Ciphertext-only cryptanalysis of short Hagelin M-209 ciphertexts. Issue 6 (2nd November 2018) - Lasry, George; Kopal, Nils; Wacker, Arno
ABSTRACT: The Hagelin M-209 was a mechanical encryption device used by the U.S. Army during World War 2 (WWII) and the Korean War, as well as by other armies and diplomatic services. The Hagelin M-209 has been the focus of extensive research by codebreaking agencies. Several ciphertext-only attacks have been published, but, those attacks are applicable only to the case of long cryptograms. In this article, the authors present a nested hill-climbing and simulated annealing algorithm for recovering the full key settings from ciphertext only, with ciphertexts as short as 500 letters, compared to a minimum of 750 to 1, 250 letters with prior methods. With this method, the authors have solved the last problem of a public Hagelin M-209 challenge contest.